2D-σ-2A type cruciform host material with silane core for highly efficient solution-processable green thermally activated delayed fluorescence organic light emitting diodes. (August 2019) - Choi, Suna; Yoon, Ji Won; Godumala, Mallesham; Kim, Hyung Jong; Park, Su Hong; Kim, Seong Keun; Lee, Hyuna; Kwon, Jang Hyuk; Cho, Min Ju; Choi, Dong Hoon
Abstract: A new solution processable cruciform tetraphenylsilane-based bipolar host material, bis(4-(9 H -carbazol-9-yl)phenyl)bis(4-(4, 6-diphenyl-1, 3, 5-triazin-2-yl)phenyl)silane (SiCT ), was designed and synthesized. Two carbazoles as donors and two diphenyl triazine moieties as acceptors were tethered to the tetraphenylsilane. SiCT showed great solubility in common organic solvents, high thermal stability, high triplet energy (T1 ∼3.0 eV), and a superior bipolar electronic nature, which are sufficient for it to function as a host material in thermally activated delayed fluorescence organic light emitting diodes (TADF-OLEDs). Consequently, the solution-processed green TADF-OLEDs employed SiCT as a bipolar host exhibited a low turn-on voltage and high external quantum efficiency (EQE) of 19.17% with a high power efficiency (PE) of 41.13 lm W −1, while control device based-on SiC as unipolar host showed a low EQE of 12.74% with a low PE of 16.13 lm W −1 . This work highlights the potential of a bipolar tetraphenylsilane derivative as a host material in solution-processable green TADF-OLEDs. Graphical abstract: Image 1 Highlights: The cruciform host material SiCT with silane core was designed and synthesized. SiCT showed high solubility, high thermal stability, high triplet energy, and a superior bipolar electronic nature. The solution-processed green TADF-OLEDs employed SiCT exhibited a low turn-on voltage and a high EQE of 19.17%.